A linguagem do corpo na obra de Hilda Hilst: "Agda" e A obscena Senhora D - Arethuza Iemini de Padua (2015)
In this paper, the relation between the work of Hilda Hilst and the performative writing are studied with specific focus on two of her proses: the story 'Agda' and the book The obscene Lady D. The search of body language in both works is taken as an initial motto to this study, in order to move through the literature of the author, her life, the main features of her characters and the theatrical approach of the literary text, with the purpose of empowering it over intermedia connections.